2005
DOI: 10.1254/jphs.fp0040850
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Src Kinase Inhibitor, M475271, Inhibits VEGF-Induced Human Umbilical Vein Endothelial Cell Proliferation and Migration

Abstract: Abstract. Vascular endothelial growth factor (VEGF) was reported to be a potent proangiogenic factor that plays a pivotal role in both physiological and pathological angiogenesis. M475271, 4-quinazolinamine, N-(2-chloro-5-methoxyphenyl)-6-methoxy-7-[(1-methyl-4-piperidinyl) methoxy]-(9Cl), is a new anilinoquinazoline derivative that showed selective inhibition of Src kinase activity and tumor growth in vivo. Here, we examined the effect of M475271 on VEGF-induced human umbilical vein endothelial cell (HUVEC) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…It was reported that increased p38 MAP kinase signaling was a feature of human and experimental diabetic nephropathy (Adhikary et al 2004). We have already reported that SB203580, a p38 MAP kinase inhibitor, suppressed cell migration induced by vascular endothelial growth factor in human umbilical vein endothelial cells (Ali et al 2005). In addition, consistent with our present findings, it has been reported that PDGF-induced p38 ffMAP kinase activation regulated cell migration in VSMCs K ISHIZAWA, N DORJSUREN and others .…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that increased p38 MAP kinase signaling was a feature of human and experimental diabetic nephropathy (Adhikary et al 2004). We have already reported that SB203580, a p38 MAP kinase inhibitor, suppressed cell migration induced by vascular endothelial growth factor in human umbilical vein endothelial cells (Ali et al 2005). In addition, consistent with our present findings, it has been reported that PDGF-induced p38 ffMAP kinase activation regulated cell migration in VSMCs K ISHIZAWA, N DORJSUREN and others .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, PI at 30 µg / ml inhibited the Akt phosphorylation induced by VEGF-A, indicating that PI induces a direct and/ or upstream inhibition of Akt in the signaling cascade induced by VEGF-A. Ali et al (24) indicated that, the PI3K inhibitor LY294002 at 10 µM inhibits the VEGF-induced migration of HUVECs. Therefore, these results suggest that inhibition of phosphorylated-Akt inhibits the VEGF-A-induced migration.…”
Section: Discussionsupporting
confidence: 66%
“…Tumors must undergo angiogenesis for survival and for metastatic spread in a limited physiological environment (30). Indeed, a previous report showed that a novel Src inhibitor, M475271, significantly inhibited VEGF-induced HUVEC proliferation, migration (31), and angiogenesis (32). It is, therefore, possible that Cx43 has a more suppressive role in growth and metastasis in vivo, where angiogenesis always contributes to tumor survival.…”
Section: Discussionmentioning
confidence: 99%